Analysis of the metric properties of a questionnaire based on the three-dimensional theory of leadership - Kausel, Edgar; Manzi, Jorge (Estudios de Administración, 2010)
The authors analyze the psychometric properties of the Inventory for Supervisor Assessment (INESUP). Based on the tridimensional leadership theory proposed by Yukl (2003), three basic categories of effective behaviors emerge: Task-oriented, Relations-oriented, and transformational. The application of the questionnaire includes two sources of information: Self-reports and upward reports (from subordinates). Comparing the self- and upward-ratings makes feedback possible, which may foster desirable behaviors and attitudes. The inventory was used on a sample composed by 10 supervisors and 89 subordinates in a financial firm. Analyses validated the instrument’s 9-factor structure and the type of scale used, as well as its reliability.